Effects of prenatal iron deficiency on neurological development and related disorders in offspring - Zhao, Zejun; Shi, Yajun; Sun, Miao; Wang, Bin (Frontiers in Nutrition, 2025)
The fetal origins of adult disease hypothesis proposes that a variety of adverse stimuli during critical development stages can impair the structure and function of fetal organs, thereby increasing the risk of disease later in life. Iron affects fetal growth and development by facilitating oxygen and electron transport and by serving as a cofactor for enzymes that affect enzyme activity. Fetal iron deficiency (ID) can result from various factors during pregnancy, including inadequate maternal iron intake, maternal obesity, diabetes, smoking, prenatal stress, and prenatal alcohol exposure. These conditions disrupt fetal brain development and are associated with neurological disorders in offspring, such as cognitive impairment, anxiety, depression, schizophrenia, and autism. However, the mechanisms by which maternal iron deficiency leads to abnormal neurological development, as well as cognitive impairment and psychiatric disorders in the offspring, remain unknown. In this review, we summarize the causes of prenatal iron deficiency, the effects of iron deficiency on brain development and behavioral phenotypes, and the potential molecular mechanisms.